A fluorescent, photochromic and thermochromic trifunctional material based on a layered metal–viologen complex. Issue 42 (8th October 2015) - Wan, Fang; Qiu, Li-Xia; Zhou, Liang-Liang; Sun, Yan-Qiong; You, Yi
Abstract : A 2D layered viologen-based zinc complex exhibits the rare discolored function of reversible photochromism and thermochromism. Interestingly, its fluorescence can be switched by visible light irradiation and heating in air. Abstract : The azide anion as an energy acceptor and an electron donor has been introduced into a metal–viologen compound to form a 2D layered viologen-based trifunctional material, which exhibits the rare discolored function of reversible photochromism and thermochromism. Interestingly, its fluorescence can be switched by visible light irradiation and heating in air.